Development and evaluation of an inertial measurement unit (IMU) system for jump detection and jump height estimation in beach volleyball - Schleitzer, S.; Wirtz, S.; Ross, J.; Eils, E. (German Journal of Exercise and Sport Research, 2022)
Wearables are commonly used in practice for measuring and monitoring performance in high-level sports. That being said, they are often designed and intended for use during sports conducted on rigid surfaces. As such, sports that are conducted on sand, e.g. beach volleyball, lack equipment that can be specifically applied in the field. Therefore, the aim of this study was to develop and validate an inertial measurement unit (IMU)-based system for automatic jump detection and jump height measurement in sand. The system consists of two IMUs, which were attached to different parts of the athletes` bodies. For validation under laboratory conditions, 20 subjects each performed five jumps on two consecutive days in a sandbox placed on force plates. Afterwards, five beach volleyball athletes performed complex combinations of beach volleyball-specific movements and jumps wearing the IMUs whilst being video recorded simultaneously. This was conducted in an ecologically valid setting to determine the validity of the IMU to correctly detect jumping actions. The results of the laboratory tests show excellent day-to-day reliability (intraclass correlation coefficient [ICC]= 0.937, two-way mixed effects, single measurement, consistency) and excellent concurrent validity (ICC= 0.946, two-way mixed effects, single rater, absolute agreement) compared to the gold standard (force plates). The accuracy in jump detection of the IMU was 100 and 97.5% in the laboratory and ecologically valid settings, respectively. Although there are still some aspects to consider when using such devices, the current findings provide recommendations regarding best practice when using such a device on a variable and unstable surface. Collectively, such a device could be applied in the field to provide coaches and practitioners with direct feedback to monitor training or match play.